KOMUNIKASI ANTARBUDAYA DALAM MEMBANGUN KERUKUNAN UMAT HINDU-ISLAM DI DESA ADAT ANGANTIGA KECAMATAN PETANG KABUPATEN BADUNG - Ida Ayu Dwi Putri Cahyanti; Ida Bagus Gede Candrawan; I Dewa Ayu Hendrawathy Putri (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2021)
The uniting of two cultures of different backgrounds which is Hinduism and Islamic in Angantiga Village is really unique. Cultural acculturation between Hindus and Moslems created a tradition that is used as guidance in strengthening intercultural tolerance to make harmony between religious believers. The problem statements of this research are: 1) How is intercultural communication between Hindus and Muslims in Angantiga Village?, 2) What are the factors of intercultural communication in building Hindu-Muslim harmony in the Angantiga village?, 3) How is the feedback of intercultural communication between Hindus and Muslims in building harmony in Angantiga village? To discover the solution to the problems stated above, the writer uses three theories, namely: Interpersonal communication theory is used in answering the first problem statement which is the intercultural communication between Hindus and Muslims in Angantiga Village, and intercultural communication theory is used to answer the second problem statement which is the factors of intercultural communication in building Hindu-Muslim harmony in the Angantiga village and Intercultural Face Negotiation theory is used to answer the feedback of intercultural communication between Hindus and Muslims in building harmony in Angantiga village. The results of this study are 1) Intercultural communication consisting of social identification, material culture, the role of relations, language, cultural stability, and beliefs and values. 2) Intercultural communication factors consisting of internal factors, external factors, and relations factors 3) Intercultural communication feedback consisting of cognitive feedback, effective feedback, and behavioral feedback